Photophysical, catalytic, and theoretical investigations of kinetically stable [Cu(2, 2′-biquinoline)(PR3)2]+ and [Cu(neocuproine)(PR3)2]+ complexes. (15th September 2022) - Domyati, Doaa; Babgi, Bandar A.; Jedidi, Abdesslem; Davaasuren, Bambar; Emwas, Abdul-Hamid M.; Jaremko, Mariusz
Graphical abstract: A set complexes were synthesized and characterized with the formula [Cu(N^N)(PMePh2 )2 ]ClO4 (4 and 6 ) or [Cu(N^N)(dppe)]ClO4 (5 and 7 )N^N = 2, 2′-biquinoline, neocuproine. Crystal structures of the neocuproine-containing complexes (5 and 7 ) were obtained and described. The methyldiphenylphosphine-containing complexes are stable in solutions (compared to PPh3 ) due to: (1) slightly better σ-donation compared to PPh3 and (2) smaller Tolman cone angle of ∼136° (compared to ∼145° in PPh3 ). In the other hand, [Cu(N^N)(dppe)]ClO4 complexes were demonstrating evidence of [Cu(N^N)2 ] +, highlighting the importance of the P-Cu-P angle. The angle P-Cu-P is around 123° in 5 compared to ∼92° in 7 . Absorption spectra of 4 and 5 exhibit low intensity broad shoulder in the visible light domain assigned as MLCT. Complexes 4 and 5 were examined in Castro-Stephens coupling reaction and found to be active, achieving complete conversion of the starting materials in contrast to the unstable [Cu(2, 2′-biquinoline)(PPh3 )2 ] + cation. Abstract: Four complexes were synthesized and characterized with the formula [Cu(N^N)(PMePh2 )2 ]ClO4 (4 and 6 ) or [Cu(N^N)(dppe)]ClO4 (5) and 7 )N^N = 2, 2′-biquinoline, neocuproine. Crystal structures of the neocuproine-containing complexes (5 and 7 ) were obtained and described. The methyldiphenylphosphine-containing complexes are stable in solutions (compared to PPh3 ) due to: (1) slightly better σ-donation compared to PPh3 and (2) smaller Tolman cone angle of ∼136° (compared to ∼145° in PPh3 ). In the other hand, [Cu(N^N)(dppe)]ClO4 complexes were demonstrating evidence of forming [Cu(N^N)2 ] + in solutions, highlighting the importance of the P-Cu-P angle. The angle P-Cu-P is around 123° in stable complex 5 compared to ∼92° in 7 . Absorption spectra of 4 and 5 exhibit low intensity broad shoulder in the visible light domain assigned as MLLCT by computational studies. While [Cu(2, 2′-biquinoline)(PPh3 )2 ] + cation was losing catalytic activity in Castero-Stephens cross-coupling over time as indicated by the low conversion rate, complexes 4 and 5 found to be active and achieved complete conversion of the starting materials.